Effect of phase shift from corals to Zoantharia on reef fish assemblages. - Igor C S Cruz; Miguel Loiola; Tiago Albuquerque; Rodrigo Reis; José de Anchieta C C Nunes; James D Reimer; Masaru Mizuyama; Ruy K P Kikuchi; Joel C Creed (PLoS ONE, 2015)
Consequences of reef phase shifts on fish communities remain poorly understood. Studies on the causes, effects and consequences of phase shifts on reef fish communities have only been considered for coral-to-macroalgae shifts. Therefore, there is a large information gap regarding the consequences of novel phase shifts and how these kinds of phase shifts impact on fish assemblages. This study aimed to compare the fish assemblages on reefs under normal conditions (relatively high cover of corals) to those which have shifted to a dominance of the zoantharian Palythoa cf. variabilis on coral reefs in Todos os Santos Bay (TSB), Brazilian eastern coast. We examined eight reefs, where we estimated cover of corals and P. cf. variabilis and coral reef fish richness, abundance and body size. Fish richness differed significantly between normal reefs (48 species) and phase-shift reefs (38 species), a 20% reduction in species. However there was no difference in fish abundance between normal and phase shift reefs. One fish species, Chaetodon striatus, was significantly less abundant on normal reefs. The differences in fish assemblages between different reef phases was due to differences in trophic groups of fish; on normal reefs carnivorous fishes were more abundant, while on phase shift reefs mobile invertivores dominated.